Zgodovinska vloga operacijskega sistema VMS pri razvoju COBISS-a - Šoštarič, Davor (Organizacija znanja, 2020)
The paper reviews, with some historical distance, the circumstances leading to the VMS operating system becoming the basis for developing and implementing the COBISS national shared bibliographic system. Following a description of the basic characteristics of VMS, the paper shows the path of its transformation in its supportive role to COBISS, as well as its omission later on.
Keywords: COBISS; OpenVMS; operacijski sistem; operating system; VAX/VMS; VMS